Informal and formal meat marketing in Ibadan, Nigeria: public health implications from microbial assessment (2021)
Introduction: informal food marketing is predominantly practiced in developing countries as it solves major social and economic challenges through the provision of employment and easily accessible food products at relatively inexpensive prices. However, such products often escape effective health and safety regulations which relatively characterize formal marketing, thus posing threats to public health. Methods: we conducted a cross-sectional microbial assessment of randomly collected raw meats (n=224) sold at selected informal (n=112) and formal (n=112) meat markets in Ibadan, south-western Nigeria for Listeria monocytogenes, Staphylococcus aureus, Escherichia coli and Salmonella spp. using standard protocols. Isolates were evaluated for antibiogram patterns by Kirby-Bauer Assay and data analysed using descriptive statistics and logistic regression. Results: overall, 75.5%, 65.2%, 61.6%, and 46.9% of the 224 samples were positive for S. aureus, L. monocytogenes, Salmonella spp, and E. coli, respectively. Significantly higher prevalences were obtained from the informal markets for S. aureus (OR=9.43; 95%CI: 0.05-0.24), L. monocytogenes (OR=9.35; 95%CI: 0.06-0.21), Salmonella spp (OR=10.00; 95%CI: 0.05-0.19) and E. coli (OR=12.99; 95%CI: 0.04-0.15) than the formal markets. The pathogens exhibited total resistance against half ofthe 14 antibiotics studied, with the least resistance to ciprofloxacin and ofloxacin. Conclusion: the significantly higher microbial contamination in meats from informal markets and associated high antibiotic resistance level portends serious public health implications of informal meat marketing. Since informal food marketing also characterizes other developing sub-Saharan African countries, synergy among local and international stakeholders to step up health and safety policies towards regulating activities at informal food markets is urgently required.